Ancient Ocean Crossings by Stephen C. Jett - Deming, David (Journal of Scientific Exploration, 2017)
This review should properly be prefaced with two caveats. First, I am not a specialist in the field of human origins. I am not an archaeologist or anthropologist, but a geologist who is generally unfamiliar with the literature covered and reviewed in this book as well as the issues and controversies. Second, I did not read the entire book. This review is based on a reading of the introduction and conclusion while skimming the rest of the text. For those who find it unsettling that a reviewer has not read a book in its entirety, I can only tell you that it is very difficult to find people who are willing to donate the time necessary to read and review long technical books. (I’m still waiting on JSE to find reviewers for books I published in 2010). Anyone who is offended by my failure to peruse this volume from front to back covers may satisfy themselves with one-hundred percent of nothing by stopping their reading at this point. Ancient Ocean Crossings examines the evidence and arguments that human cultures in the Western Hemisphere were influenced by occasional contacts with ocean voyagers before Christopher Columbus arrived in the Americas in 1492. As the author notes, it’s now conceded that Vikings established a few settlements in North America hundreds of years before Columbus, yet these colonies were short-lived and apparently had little to no influence on American Indians. The ocean crossings referred to in the text are hypothetical voyages that may have occurred in the ten thousand years before Europeans first set foot in the Americas. There are some striking and unexplained cultural similarities between native peoples of the Old World and the Americas. These include “technical complexities of weaving and dyeing that are shared between southern Asia and the Central Andean region of South America, “stepped temple pyramids that are oriented to the cardinal directions in both Mesoamerica and Cambodia, and the belief “in both China and Mesoamerica, that raw jade can be discovered in nature owing to ‘exhalations’ coming from the stone” (p. 5).